Cinnamomum verum component 2-methoxycinnamaldehyde: a novel antiproliferative drug inducing cell death through targeting both topoisomerase I and II in human colorectal adenocarcinoma COLO 205 cells - Tsai, Kuen-daw; Cherng, Jonathan; Liu, Yi-Heng; Chen, Ta-Wei; Wong, Ho-Yiu; Yang, Shu-mei; Chou, Kuo-Shen; Cherng, Jaw-Ming (Food & nutrition research, 2016)
Cinnamomum verum is used to manufacture the spice cinnamon. In addition, the plant has been used as a Chinese herbal medication. We investigated the antiproliferative effect of 2-methoxycinnamaldehyde (2-MCA), a constituent of the cortex of the plant, and the molecular biomarkers associated with tumorigenesis in human colorectal adenocarcinoma COLO 205 cells. Specifically, cell viability was evaluated by colorimetric assay; apoptosis was determined by flow cytometry and morphological analysis with bright field, acridine orange, and neutral red stainings, as well as comet assay; topoisomerase I activity was determined by assay based upon DNA relaxation and topoisomerase II by DNA relaxation plus decatentation of kinetoplast DNA; lysosomal vacuolation and volume of acidic compartments (VACs) were determined by neutral red staining. The results demonstrate that 2-MCA inhibited proliferation and induced apoptosis as implicated by mitochondrial membrane potential (ΔΨ m ) loss, activation of both caspase-3 and -9, increase of annexin V + PI + cells, as well as morphological characteristics of apoptosis. Furthermore, 2-MCA also induced lysosomal vacuolation with elevated VAC, cytotoxicity, and inhibitions of topoisomerase I as well as II activities. Additional study demonstrated the antiproliferative effect of 2-MCA found in a nude mice model. Our data implicate that the antiproliferative activity of 2-MCA in vitro involved downregulation of cell growth markers, both topoisomerase I and II, and upregulation of pro-apoptotic molecules, associated with increased lysosomal vacuolation. In vivo 2-MCA reduced the tumor burden that could have significant clinical impact. Indeed, similar effects were found in other tested cell lines, including human hepatocellular carcinoma SK-Hep-1 and Hep 3B, lung adenocarcinoma A549 and squamous cell carcinoma NCI-H520, and T-lymphoblastic MOLT-3 (results not shown). Our data implicate that 2-MCA could be a potential agent for anticancer therapy.